Expanding Collective Efficacy Theory to Reduce Violence Among African American Adolescents - Whipple, Christopher R. (Journal of interpersonal violence, 2021)
Community violence is a complex phenomenon, and many theories have been put forth to explain the causes of community violence and disparities in community violence across neighborhoods. One notable theory, collective efficacy theory (CET), posits that collective efficacy (i.e., a neighborhood’s social cohesion and informal social control) mediates the association between concentrated disadvantage and community violence. As CET theorizes an inverse feedback loop between collective efficacy and community violence, collective efficacy could mitigate the link between neighborhood disadvantage and community violence. The current study examines the reciprocal association between collective efficacy and community violence exposure using data from 604 low-resourced, urban African American ninth-grade students from a large Midwestern city. Data were collected at 6-month intervals over 2 years. Significant cross-sectional associations were found between each of the collective efficacy constructs (social cohesion and informal social control) and community violence exposure, although no significant longitudinal cross-lagged associations were found. There were positive cross-sectional associations between (a) collective efficacy and community violence exposure and (b) informal social control and community violence exposure; however, the association between social cohesion and community violence exposure was negative. Associations between overall collective efficacy, as well as its subscales, and community violence exposure were consistent with hypothesized directions for social cohesion, but not for collective efficacy or informal social control. Findings support the use of collective efficacy as two constructs, rather than a single construct as proposed by Sampson et al. Implications for expanding original assumptions of CET are discussed.